In silico analysis of SARS-CoV-2 papain-like protease potential inhibitors. Issue 61 (1st December 2021) - Elseginy, Samia A.; Anwar, Manal M.
Abstract : The emergent outbreak caused by severe acute respiratory syndrome coronavirus 2 continues spreading and causing huge social and economic disruption. Abstract : The emergent outbreak caused by severe acute respiratory syndrome coronavirus 2 continues spreading and causing huge social and economic disruption. Papain-like protease (PLpro) has a crucial role in the cleavage of viral polyproteins, and disruption of host responses. PLpro is considered an important goal for the development of SARS-CoV-2 inhibitors. ZINC101291108 (lead 1) and ZINC16449029 (lead 2) were identified as potent SARS-CoV-2 PLpro inhibitors with IC50 values of 0.085 μM and 0.063 μM, respectively. Molecular dynamics simulations (MD) were carried out for lead 1, 2 and several reported SARS-CoV-2 inhibitors. Analysis results of the simulations confirmed the stability of both compounds and showed that they adopted two confirmations along the simulation period. The per-residue decomposition results revealed that the key residues involved in inhibitor binding were E167, P247, P248, Y264, Y268 and Q269. H-bond analyses showed H-bonds with G266 and N267 and salt bridges with G209 and Y273, which are essential for strengthening the substrate-binding pocket. Both inhibitors showed hydrophobic interactions with the S4 site and BL2 loop residues. The RMSD of the BL2 loop with the two inhibitors was investigated, and the results showed that the Y268 and Q269 BL2 loop residues moved outward to accommodate the large size of lead 2. The van der Waals interaction was the main energy contribution that stabilized lead 2, while van der Waals and electrostatic interactions were the main energy contributions stabilizing lead 1. Rational design strategies were suggested to replace the 2-(2-hydroxybenzylidene) hydrazine moiety with naphthalene or nitrobenzene at the P4 position of lead 2 and introduce polar substituents as aniline and benzoate groups at position P1 to enhance hydrophobic interactions and H-bonds, respectively.